Brody's ghost. Book 5 - Crilley, Mark (Dark Horse Books, 2014)
Down on his luck street musician Brody wanted nothing to do with teenaged ghost Talia or her search for the Penny Murderer until a psychic vision revealed his ex-girlfriend as the killer's next target! Now racing against the clock to save her, Brody learns that Talia was among the Penny Murderer's first victims and gets a pivotal lead in the form of Talia's mother! But to follow it, Brody has to break ties with Talia, just when he needs her help to escape gangsters and the police!